Influence of the Knowledge of Selected Concepts on the Organization Process Maturity - Katarzyna RAGIN-SKORECKA (Communications of International Proceedings, 2021)
Aim: The article presents the results of research showing the relationship between the knowledge of certain concepts related to process management and the level of process maturity. The subject of research is a response to the identified research gap regarding the indication of which of the concepts used in the process approach have the greatest impact on the organization process maturity. Methodology: The results of the study are part of a broader study of process maturity and management methods used. The research process included: preparation of the questionnaire and CATI survey (44 respondents). Due to the small number of collected data, the analysis was performed using the grey system theory. Findings: The obtained research results allowed to determine how important it is to understand given concepts related to the process approach in order to achieve a higher level of process maturity. Conclusions: The obtained research results broadened the knowledge about the process approach in organizations. On the threshold of the widespread digital transformation of processes, it is important to properly implement process changes, relying on an unambiguous conceptual apparatus.
Keywords: Process Maturity; Grey System Theory; Organization